Blockchain Technology: Revolutionizing Financial Operations through Transparency and Security - Upendar Reddy Gade, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the transformative impact of blockchain technology on financial operations, focusing on its architectural foundations, security mechanisms, and practical applications. The article explores how blockchain's distributed ledger technology revolutionizes transaction processing and verification through advanced cryptographic protocols and consensus mechanisms. The article encompasses the evolution of smart contracts, their role in automating financial agreements, and the implementation of robust security frameworks. The article also investigates blockchain's contribution to regulatory compliance and audit capabilities, while addressing future developments in the technology's integration with artificial intelligence and cross-chain interoperability protocols. The article demonstrates blockchain's significant potential in creating more efficient, transparent, and secure financial systems while highlighting the importance of balanced implementation strategies that consider both performance optimization and security requirements.
Keywords: Blockchain Architecture; Cryptographic Security; Financial Operations; Smart Contracts; Transaction Processing